Morphogenesis and Morphometry of Middle Ear Ossicles in Nellore Sheep Fetus - Karunasri V; Nagamalleswari Y; Raju N K B (Indian Journal of Veterinary Anatomy, 2024)
The development of middle ear ossicles in sheep has not been reported previously. The present study was designed to report the major events in the time line of development in the morphogenesis of middle ear ossicles. The fetuses were categorized into group I (< 7.0 cm CRL), group II (< 25.0 cm CRL) and group III (>25.0 cm CRL) on the basis of crown rump length (CRL) that ranged between 22 to 145 days. At 58 days (10 cm CRL) fetal age, the tympanic cavity was filled with jelly like fluid in which three cartilaginous tiny ossicles malleus, incus and stapes were observed towards the epitympanic region. At 75 days (16.5 cm CRL), the malleus showed a handle, head, neck and two processes. Rostral process of malleus was absent in sheep fetuses. At 82 days (19 cm CRL), incus differentiated with a body, long process and short process. Stapes appeared as triangular to trapezoid in shape with centrally located obturator foramen by 85 days (20 cm CRL). It consisted of head, base, rostral crus, caudal crus and foot plate at this fetal age. Morphometric analysis of middle ear ossicles revealed that the average length, width in different parts of these ossicles increased significantly between different age groups.